Predictors of 30-day hospitalization in patients with worsening heart failure receiving outpatient intravenous diuretics - Willemijn A. van Maarschalkerwaart; Eric Wierda; Dominique de Boer; Nini H. Jonkman; Eric Boersma; Jasper J. Brugts; Loek van Heerebeek (PLoS ONE, 2026)
Background Outpatient intravenous (IV) diuretic treatment is an effective and safe strategy for worsening heart failure (WHF). Still, hospitalization cannot be avoided in a substantial portion of patients and potential predictors of HF hospitalization (HFH) are eagerly awaited. Aim We aimed to identify predictors of HFH after outpatient IV diuretic treatment for WHF, in order to improve the selection of patients who qualify for successful outpatient IV diuretic treatment. Methods and results We studied WHF patients receiving intravenous diuretics in an outpatient day-care setting in one of two Dutch hospitals. A total of 366 patients from hospital A were used to identify predictors of 30-day HF (re-)hospitalization (HFH), which occurred in 88 (24.0%). Mean age was 76 years, 57% were male and 49% had ejection fraction below 40%. Age, eGFR, NT-proBNP, sodium, and haemoglobin were identified as predictors of HFH. The multivariable logistic regression model containing these factors had acceptable calibration and discrimination (AUC 0.73). The performance of the model was less favorable in the 127 patients from hospital B (29 patients with 30-day HFH), with AUC 0.65 and suboptimal calibration, indicating overestimation of risk. Doubling of NT-proBNP plasma levels and higher ambulatory oral loop diuretic dosages were strong predictors of mortality and HFH at 6 months in hospital A. Conclusion In patients with WHF receiving outpatient day-care intravenous diuretic treatment, age, eGFR, NT-proBNP, sodium and haemoglobin predicted 30-day HFH. These factors may guide decisions on day-care treatment versus hospitalization, but require further validation Fig 2.